Out of Many Faiths Religious Diversity and the American Promise - Patel, Eboo (Our Compelling Interests, 2019)
A timely defense of religious diversity and its centrality to American identityAmerica is the most religiously diverse nation on the planet. In today’s volatile climate of religious conflict and distrust, how do we affirm that the American promise is deeply intertwined with how each of us engages with people of different beliefs? Eboo Patel, former faith adviser to Barack Obama, provides answers to this timely question. In this thought-provoking book, Patel draws on his personal experience as a Muslim in America to examine the importance of religious diversity in the nation’s cultural, political, and economic life. He explores how religious language has given the United States some of its most enduring symbols and inspired its most vital civic institutions—and demonstrates how the genius of the American experiment lies in its empowerment of all people